2016
DOI: 10.1002/ece3.2621
|View full text |Cite
|
Sign up to set email alerts
|

An exception to the matched filter hypothesis: A mismatch of male call frequency and female best hearing frequency in a torrent frog

Abstract: The matched filter hypothesis proposes that the tuning of auditory sensitivity and the spectral character of calls will match in order to maximize auditory processing efficiency during courtship. In this study, we analyzed the acoustic structure of male calls and both male and female hearing sensitivities in the little torrent frog (Amolops torrentis), an anuran species who transmits acoustic signals across streams. The results were in striking contradiction to the matched filter hypothesis. Auditory brainstem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Although structural complexity might help explain low levels of copulation success on leaf and pine litter (see earlier discussion of microhabitat preference), pairs remain capable of mating in the absence of vibratory and visual signals. Similar mismatches have been observed in other communication systems as well (Jain & Balakrishnan, 2012;Schmidt & Balakrishnan, 2015;Smith et al, 2011;Smith, van Staaden, & Carleton, 2012;Zhao et al, 2017).…”
Section: Copulation Success Across Substrate Types and Light Levelssupporting
confidence: 85%
“…Although structural complexity might help explain low levels of copulation success on leaf and pine litter (see earlier discussion of microhabitat preference), pairs remain capable of mating in the absence of vibratory and visual signals. Similar mismatches have been observed in other communication systems as well (Jain & Balakrishnan, 2012;Schmidt & Balakrishnan, 2015;Smith et al, 2011;Smith, van Staaden, & Carleton, 2012;Zhao et al, 2017).…”
Section: Copulation Success Across Substrate Types and Light Levelssupporting
confidence: 85%
“…The results of a previous study indicate that the dominant frequency of natural male advertisement calls (4.3 kHz) is substantially mismatched with female auditory frequency tuning (1.6 kHz) in little torrent frogs, despite the fact that low-frequency calls with a dominant frequency equal to 1.6 kHz are attractive to females compared to white noise (Zhao et al 2017 ). Furthermore, females prefer high-frequency calls (dominant frequency of 4.3 kHz) to low-frequency calls, regardless of whether they are listening in silent, low-noise or high-noise environments (Zhao et al 2017 ). To test the hypothesis that stream noise can be used by females as a cue reflecting information about the microhabitat during mate choice, we compared the females’ preferences for stimulus pairs constructed with synthetic male calls (high frequency or low frequency) and stream noise of varied SNR.…”
Section: Introductionmentioning
confidence: 98%
“…The amplitude of the environmental noise level experienced by the concave‐eared torrent frog is comparable to that of the little torrent frog (Zhang et al, ); however, call amplitude in the concave‐eared torrent frog can increase from 70–75 to 80–85 dB when exposed to 53–83 dB noise (Shen & Xu, ). In a previous study, ambient noise and call characteristics were compared across three streamside species (Zhao, Wang, et al, ). The results showed that the little torrent frog had lower dominant frequency ( A. torrentis : 4,318 Hz; Micrixalus saxicola : 4,771 Hz; Staurois parvus : 5,578 Hz) and higher call amplitude (signal/noise: A. torrentis : 80.3/62.4; M. saxicola : 69/67; S. parvus : 62/72) when compared to the other two species.…”
Section: Discussionmentioning
confidence: 99%
“…Sound recordings and measurements followed the procedures described in detail previously (Zhao, Wang, et al, ). Briefly, once calling males were located in the stream, the natural calls and running water were recorded immediately using a directional microphone (Sennheiser ME66 with K6 power module) connected to a digital recorder (Marantz PMD 660, 16 bit, 44.1 kHz), while the sound pressure levels of these sounds (SPLs, A‐weighted) were simultaneously measured using a sound level meter (AWA 6291, Hangzhou Aihua Instruments Co.), at a precise distance of 1 m. Since sound radiation varies in its directionality, the microphone and sound level meter were directed along the snout‐vent orientation of the subject.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation